The effect of using some physical exercises with wet-cupping in relieving lower back pain among weightlifters - HADJI, Hamada (sports creativity, 2023)
his study aimed to identify the effect of using some physical exercises with wet cupping in relieving low back pain among weightlifters .The researcher used the experimental method of one group design with pre and post measurement, this study was conducted on (8) weightlifters suffering from low back pain, who were referred to Al-Shifa Clinic for Physiotherapy in Barika, Batna Province, their ages ranged between (22-35 years).The program was implemented over a period of (8) weeks, with two sessions per week of physical exercises, and one session of wet cupping every two weeks. Four tests were used to measure the range of motion, the graded pain scale, and the (Ronald Morris) scale to measure the degree of disability resulting from low back pain. The results showed that there are statistical differences between the pre and post measurements of the sample, in favor of the post measurement in all variables of the study